Nassarius foveolatus (Gastropoda, Nassariidae), a new record of an exotic species in Brazil - Gernet, Marcos de Vasconcellos; Belz, Carlos Eduardo; Baggio, Rafael Antunes; Birckolz, Carlos João; Santos, Elizângela da Veiga; Simone, Luiz Ricardo Lopes de; Abbate, Daniel; Metri, Rafael (Papéis Avulsos de Zoologia, 2019)
Exotic species are those that occur in an area beyond their natural limit and they are considered invasive when they cause harm to the economy, environment, or human health. In coastal environments, ballast water and inlays on the hull and other parts of vessels are the main ways of introducing invasive aquatic alien species. Nassarius foveolatus (Dunker, 1847) is native from the Central and East Indian Ocean to the East China Sea. The first specimens (empty shells) of N. foveolatus were collected manually on November 11, 2017 on the Rocio footbridge, located in the Paranaguá Estuarine Complex, on the coast of the State of Paraná, southern Brazil. Posteriorly, live specimens were collected in other localities of this bay. It is already possible to infer that the specimens of N. foveolatus occur together with the native specimens of N. vibex (Say, 1822), having the same niche. As previously only N. vibex existed in that place, at least a displacement of this native species has been occurred. However, certainly future ecological studies may confirm this displacement and additional consequences to the local ecosystem, as nassariids can be predators and scavengers. Control procedures should be also greatly implemented.